Sources, trends and regional impacts of fine particulate matter in southern Mississippi valley: significance of emissions from sources in the Gulf of Mexico coast - M.-C. Chalbot; B. McElroy; I. G. Kavouras (Atmospheric Chemistry and Physics, 2013)
The sources of fine particles over a 10 yr period at Little Rock, Arkansas, an urban area in the southern Mississippi Valley, were identified by positive matrix factorization. The annual trends of PM2.5 and its sources, and their associations with the pathways of air mass backward trajectories were examined. Seven sources were apportioned, namely, primary traffic particles, secondary nitrate and sulphate, biomass burning, diesel particles, aged/contaminated sea salt and mineral/road dust, accounting for more than 90% of measured PM2.5 (particles with aerodynamic diameter less than 2.5 μm) mass. The declining trend of PM2.5 mass (0.4 μg m−3 per year) was related to lower levels of SO42− (0.2 μg m−3 per year) due to SO2 reductions from point and mobile sources. The slower decline for NO3− particles (0.1 μg m−3 per year) was attributed to the increasing NH3 emissions in the Midwest. The annual variation of biomass burning particles was associated with fires in the southeast and northwest US. Of the four regions within 500 km from the receptor site, the Gulf Coast and the southeast US accounted cumulatively for more than 65% of PM2.5 mass, nitrate, sulphate and biomass burning aerosol. Overall, more than 50% of PM2.5 and its components originated from sources outside the state. Sources within the Gulf Coast and western Gulf of Mexico include 65% of the busiest ports in the US, intense marine traffic within 400 km of the coast burning rich in S diesel, and a large number of offshore oil and natural gas platforms and many refineries. This approach allowed for the quantitative assessment of the impacts of transport from regions representing diverse mixtures of sources and weather conditions for different types of particles. The findings of this effort demonstrated the influences of emission controls on SO2 and NOx on PM2.5 mass, the potential effect of events (i.e. fires) sensitive to climate change phenomena on air pollution and the potential of offshore activities and shipping emissions to influence air quality in urban areas located more than 1000 km away from the sources.